Analysis of the Thoughts of Abdurrahman An-Nahlawi and Zakiah Daradjat on Education in Muslim Families - Sarianto, Debi; Amir, Yusri; Satrial, Ardi; Rahman, Abd; Rahman, Ikhwan; Hidayat, Rahmad (Al-Hashif: Jurnal Pendidikan dan Pendidikan Islam, 2024)
The thoughts of Abdurrahman An-Nahlawi and Zakiah Daradjat present a perspective that emphasizes the importance of Islamic education, which begins in the home environment, being based on the Qur'an and translated into daily life practices. This approach ensures that Muslim families are not only the primary learning institution but also the main fortress in instilling Islamic values. This study aims to explain the concept of Islamic education in family development according to the two figures, identify similarities and differences from the perspective of sources and application of education, and examine the relevance of the application of the concept in the formation of children's morals. This study uses a qualitative approach with a literature review-based figure study method, where data is collected through literature studies that include primary sources in the form of works by Abdurrahman An-Nahlawi and Zakiah Daradjat, as well as secondary sources such as books and other relevant scientific works. The results of the analysis reveal that although both figures place the Qur'an as the main source of Islamic education, there are differences in the emphasis of methods and interpretations of the application of Islamic values ​​in family life. Their fundamental similarity lies in the belief that Islamic education at home must be able to shape the character and morals of children holistically, while the differences arise from the practical approach and social context faced by each thinker. The results of this study can contribute to strengthening the concept of Islamic education in the family as a strategic effort to foster children's morals, as well as providing direction for educators and policymakers in designing educational programs that are by the principles of Islamic law and the demands of the development of the times.